Merdeka Day reflections: Don't be swayed by manipulations of a few - Abd Razak, Dzulkifli (2010)
THE "Ganyang Malaysia" sentiment has boiled over yet again in our neighbouring country. This time, it has a special significance as Malaysians are in the midst of celebrating independence day today, and Malaysia Day on Sept 16.